2015
DOI: 10.15406/mojor.2015.03.00085
|View full text |Cite
|
Sign up to set email alerts
|

The Three D’s of Insurance: Delay, Deny and Do not Pay Analysis of Collection Rates for Illinois Workers’ Compensation Patients

Abstract: The three D's of insurance: delay, deny and do not pay analysis of collection rates for Illinois workers' compensation patients 268

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…An injured worker in a low densely populated area without a claim number was unable to gain access to a primary care doctor in our cohort (100% denial rate). Even a patient with an accepted claim number in densely populated Cook County, IL had a 52% chance of being denied access to care with an orthopedic surgeon (Table 3 & 4). Ultimately, we need to recognize that the purpose of workers' compensation was to provide timely access to appropriate medical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An injured worker in a low densely populated area without a claim number was unable to gain access to a primary care doctor in our cohort (100% denial rate). Even a patient with an accepted claim number in densely populated Cook County, IL had a 52% chance of being denied access to care with an orthopedic surgeon (Table 3 & 4). Ultimately, we need to recognize that the purpose of workers' compensation was to provide timely access to appropriate medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that 32% of workers' compensation claims in our practice are never paid while the average time in collections was 3.6 years (1,342 days). 4 These realities result in a cost/benefit analysis that leads many providers to close their offices to the treatment of the injured worker. This lack of appropriate access has a subsequent effect of making many who are legitimately injured while at work due to no fault of their own, financially destitute.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the system often becomes adversarial where access to appropriate care is limited through a process of delay and denial. 23 We have previously demonstrated that timely access to appropriate treatment can decrease medical costs and time to Maximum Medical Improvement (MMI) in the working population. 24 Most studies that have evaluated outcomes in the workers compensation population have focused on subjective shoulder outcome scores and not functional outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reviewed our workers compensation accounts receivables in our orthopedic practice from 2006 until 2014. 3 The collection rate for the workers compensation population was 68% (32% of claims never paid) while the average time in collections was 3.6 years (1,342 days) for active claims. Review of the statistical data demonstrated that 98% of all accounts receivable (AR) belonged to workers compensation (87%) patients and personal injury claims (11%), even though they represented 58.8% and 5.2% of the total claims respectively.…”
mentioning
confidence: 99%